Modeling and analysis of fractional order Ebola virus model with Mittag-Leffler kernel - Muhammad Farman (Elsevier, 2022)
In this article, we presented a nonlinear time-fractional mathematical model of the Ebola Virus in order to understand the outbreak of this epidemic disease. Ebola virus is a highly contagious disease that can be spread in the population depending upon the number of individuals and their dynamics in the community. The Caputo and Atangana Baleanu fractional derivative operators are employed to get the solution of the system of fractional differential equations. The qualitative analysis has been made for the fractional-order model. Fixed-point theorem and an iterative schemes are used to get the existence and uniqueness. The actual behavior of the time-fractional model has been obtained by employing Laplace Adomian Decomposition technique. Finally, numerical results have been established for the system of fractional differential equations with simulations to demonstrate the impacts of the fractional-order parameters on the proposed system to achieve the theoretical outcomes and a comparison has been made with the Caputo for better analysis.